P-HPB-17: Pancreatic duct ascariasis: Case series - Patil, Amol (Endosc Ultrasound, 2017)
BACKGROUND AND OBJECTIVES: Ascaris lumbricoides is a common cause of acute pancreatitis in the developing countries. Ultrasonography (USG) is a useful tool for the diagnosis; however, the diagnosis may be false negative in up to 30% of cases. MATERIALS AND METHODS: During a study period of 10 years, 15 cases of pancreatic ascariasis were diagnosed by USG/endoscopic ultrasound (EUS). Thirteen patients presented with symptoms of acute pancreatitis. Of 13 patients, nine presented with first episode of idiopathic pancreatitis while four presented with idiopathic recurrent acute pancreatitis. One patient had biliary colic and one patient presented with acute cholangitis. Twelve patients had mild pancreatitis while only one had moderate pancreatitis. Only two cases were diagnosed with USG while 13 patients were diagnosed with EUS. The patients underwent side viewing endoscopy/endoscopic retrograde cholangiopancreatography under the same sedation after EUS if EUS revealed biliary/pancreatic ascariasis. Of 15 patients, 14 underwent side viewing endoscopy with removal of live single/multiple worms with rat tooth forceps/Dormia basket in 13 patients. Two patients were managed conservatively with repeat USG showing the absence of ascariasis. There were no complications. RESULTS: EUS features were single or multiple linear hyperechoic structure without acoustic shadowing in the pancreas divisum with central anechoic tube representing alimentary canal of the worm. Live roundworms were removed from papilla without undertaking sphincterotomy. In endemic areas, sphincterotomy facilitates the risk of migration of worms into the common bile duct. CONCLUSIONS: Ascariasis-induced acute pancreatitis is mild and EUS is the investigation of choice. The recurrence is rare and treatment is side viewing endoscopy with removal of worms.